Lean production requirements and its impact on project success - application research in Central Bureau of Statistics projects - اسعد كاظم نايف,; سحر فيض الله محمد, (Iraqi Journal for Administrative Sciences, 2025)
The research has Two change interaction to gether to build a clear structure to use it in the Iraqi society specially, these change which are related (Lean Production Requirements and Project Success) . The main Problem is increasing waist processes in cost, Human resources and time needed for Projects accomplishmet . The researchers select the projects of Centeral Organization of statistic as a study sample by determining (123) person to answer the quastion . The main Conclusions represent :- - The more important point is to be care on selecting and training effective leaders and experiment skills team-works for projects . - The study sample hadn’t clear vision about the practical and behavioral sides for lean-production requirements .